2022
DOI: 10.1021/acs.orglett.2c00085
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Photocatalytic Radical Rearrangement in N-Indolyl Carbonates

Abstract: A new type of sp3-like N-centered radical has been generated by selective energy transfer catalysis. Upon photoexcitation, homolytic N–O bond cleavage of N-indolyl carbonate in the presence of an Ir complex produced N- and O-centered radicals. The high spin density at the C3 position of indole led to radical recombination with the O-centered radical, affording valuable 3-oxyindole derivatives without decarboxylation. Transformations of the desired products into various molecules were also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…68 Recently we envisaged the skeletal rearrangement of N-indolyl carbonates 13 through homolytic N−O bond cleavage followed by [3,3]-radical recombination in the presence of [Ir−F] (Scheme 7). 62 The redox potentials of 13a…”
Section: N−o Bond Activation In N-indolyl Carbonatesmentioning
confidence: 99%
See 2 more Smart Citations
“…68 Recently we envisaged the skeletal rearrangement of N-indolyl carbonates 13 through homolytic N−O bond cleavage followed by [3,3]-radical recombination in the presence of [Ir−F] (Scheme 7). 62 The redox potentials of 13a…”
Section: N−o Bond Activation In N-indolyl Carbonatesmentioning
confidence: 99%
“…Careful selection of the substrate and photocatalyst in terms of compatible triplet energies and mismatched redox potentials is a prerequisite for the success of the EnT process. Figure shows substrates and photocatalysts used in N–O bond activation by selective EnT, including oximes (aryl oximes, oxime esters, , oxime carbonates, , and oxime (gly)­oxalates), 1,2,4-oxadiazolines, , phthalimide enolates, N -indolyl carbonates, N -benzoyloxy carbamates, and N -enoxybenzotriazoles, with a disclosure of their triplet excited state energies. Our laboratory (often in collaboration with the You and Shin groups) utilized a diverse range of substrates such as 1,2,4-oxadiazolines, oxime esters, N -indolyl carbonates, and N -enoxybenzotriazoles.…”
Section: N–o Bond Activation By Energy Transfer Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction potential ( E red ) of 1a (−1.54 V vs SCE in CH 3 CN) and 3a (−1.56 V vs SCE in CH 3 CN) were lower than the excited state oxidation potential ( E * ox ) of the [Ir III ]-catalyst (−1.04 V vs SCE, CH 3 CN), and the oxidation potentials ( E ox ) of 1a (1.69 V vs SCE in CH 3 CN) and 3a (2.16 V vs SCE in CH 3 CN) were more positive than the excited state reduction potential ( E * red ) of the [Ir III ]-catalyst (1.39 V vs SCE, CH 3 CN) (see Figure S8 in the SI) . These results indicated that both reductive and oxidative electron transfer between photoexcited [Ir III ]-catalyst and substrates ( 1a and 3a ) were thermodynamically forbidden.…”
mentioning
confidence: 92%
“…6 The Shin and our groups have recently disclosed photosensitized energy transfer (EnT) processes of N-indolyl carbonates (Scheme 1a(v)). 7,8 The homolytic scission of N−O bond via EnT generated both N-and O-centered radicals, 9 which were further involved in radical-radical recombination to afford formal [3,3]-shifted 3-oxyindole products. 7,10 Building on these findings, we have developed a new approach using Ag-catalysis to achieve the concerted [3,3]-rearrangement of N-oxyindoles to produce 3-oxyindole derivatives with a broader substrate scope, including ester derivatives which were not compatible with our previous photocatalytic process (Scheme 1b).…”
mentioning
confidence: 99%